Durability Analysis of Natural Lime Concrete - Tan, Yeong Yu; Doh, Shu Ing; Chin, Siew Choo (Springer Nature, 2018)
Concrete is known to be durable and dependable material since it is resistance to weathering action and chemical attacks while maintaining its engineering properties. However, carbon dioxide produced by the cement industries had caused severe environmental pollution. To minimize carbon dioxide emission into the atmosphere, eggshell wastes are treated as partial cement replacement in this study. The eggshell was oven-dried at 105.5 °C for 24 h before grinding it into powder passing through sieve size 45 µm. Eggshell powder was used as partial cement replacement at 5, 10, 15 and 20%. The performance of the concrete mix was evaluated against control concrete mix. The specimens were tested on acid attack and sulphate attack. The concrete specimens were prepared in the form of cubes and then subjected to water curing for 28 days before immersed in sulphuric acid solution for 1800 h and sodium sulphate for 50 weeks respectively. From the analysis, it is observed that reduction of compressive strength of the concrete cubes for the acid attack and sulphate attack reduce gradually when the eggshell powder increase.